The Relationship of Serum Soluble Fas Ligand (sFasL) Level with the Extent of Coronary Artery Disease - Sahinarslan, Asife; Boyaci, Bulent; Kocaman, Sinan Altan; Topal, Salih; Ercin, Ugur; Okyay, Kaan; Bukan, Neslihan; Yalçin, Ridvan; Cengel, Atiye (International Journal of Angiology, 2012)
Fas/Fas ligand system contributes to the programmed cell death induced by myocardial ischemia. We investigated whether serum soluble Fas ligand (sFasL) level is independently related with the severity and extent of angiographically assessed coronary artery disease (CAD). We included 169 patients in this study. Two groups were formed based on the existence of a lesion on coronary angiography. First group included patients with normal coronary arteries (NCA; n = 53). Patients with atherosclerotic lesions were included in the second group (n = 116). We used the coronary vessel score (the number of the coronary arteries with a lesion leading to ≥ 50% luminal obstruction) and the Azar score to determine the extent and the severity of CAD. Standard enzyme-linked immunosorbent assay kits were used to measure serum sFasL levels. The serum sFasL level was higher in patients with CAD than in patients with NCA (0.52 ± 0.23 mU/mL vs. 0.45 ± 0.18 mU/mL, p = 0.023). The sFasL level correlated with Azar score (r = 0.231, p = 0.003) and with coronary vessel score (r = 0.269, p < 0.001). In the multivariate analysis, we found that age (beta: 0.188, p = 0.008), gender (beta: 0.317, p < 0.001), diabetes mellitus (DM; beta: 0.195, p = 0.008), and sFasL level (beta: 0.209, p = 0.003) were independently related with Azar score. When we used coronary vessel score as the dependent variable, we found that age (p = 0.020), gender (p < 0.001), DM (p = 0.006), and sFasL level (p = 0.001) were independent predictors. Serum sFasL level is associated with angiographically more severe CAD. Our findings suggest that sFasL level may be a biochemical surrogate of severe coronary atherosclerosis.
Keywords: soluble fas ligand; ischemic heart disease; atherosclerosis; apoptosis